2020
DOI: 10.3390/healthcare8040460
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Barriers to Telerehabilitation-Based Physical Therapy Practice in Saudi Arabia

Abstract: (1) Telerehabilitation (TR) is a part of telemedicine involved in providing rehabilitation services to people in remote locations. TR in physical therapy in the kingdom of Saudi Arabia is still in its infancy and its implementation may pose different challenges in the physical therapy settings. The purpose of this nation-wide survey is to explore physiotherapists (PTs) knowledge, attitudes, and barriers towards implementation of TR in physical therapy settings; (2) Methods: A 14 item questionnaire was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
64
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 24 publications
(12 reference statements)
4
64
0
1
Order By: Relevance
“…We observed that while PR providers have a reasonable to good level of understanding, their practice is limited due to organizational and economic factors. Our study findings corroborate a recent Saudi Arabian survey about the lack of telehealth-based physical therapy practices, though the study showed increased telemedicine knowledge among physiotherapy experts ( Aloyuni et al., 2020 ). Similarly, patients responding to our survey expressed a high level of interest in telerehabilitation services but expressed concern about the availability and expertise of telehealth-based PR treatments.…”
Section: Discussionsupporting
confidence: 90%
“…We observed that while PR providers have a reasonable to good level of understanding, their practice is limited due to organizational and economic factors. Our study findings corroborate a recent Saudi Arabian survey about the lack of telehealth-based physical therapy practices, though the study showed increased telemedicine knowledge among physiotherapy experts ( Aloyuni et al., 2020 ). Similarly, patients responding to our survey expressed a high level of interest in telerehabilitation services but expressed concern about the availability and expertise of telehealth-based PR treatments.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with previous studies wherein PTs reported that limited access to technical support at their facilities was behind them not adopting telerehabilitation [ 10 , 14 ]. In contrast, PTs in Saudi Arabia reported lower utilization of telerehabilitation services by patients during the COVID-19 pandemic, despite the availability of technical support [ 27 ]. In the present study, the interview results reveal that the managers of the physiotherapy departments comprehended the need for telerehabilitation services during the pandemic, so some of their departments had started offering telerehabilitation services in order to prevent the spread of COVID-19, as well as to reduce waiting lists, facilitate patients’ access, and decrease patients’ transport time to attend clinics.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of suitable training in the use of equipment to practise telerehabilitation was another barrier that was highlighted by most of the PTs, as technology barriers are considered a major issue in implementing telehealth systems [ 28 ]. In Saudi Arabia, PTs reported a lack of technical and staff skills as the main barriers to telerehabilitation [ 27 ]. The physiotherapy managers confirmed these barriers, as well as the disadvantages of telerehabilitation, which include a lack of hands-on skills, difficulty in practising real physiotherapy via video-calls, and the inability to create the same level of trust between specialists and patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other barriers were technical issues, the lack of information, the lack of involvement in planning, the shortage of exposure to e-healthcare information, resistance to change, the lack of using hardware and software, low connectivity, staff skill problems, and high-cost provider's willingness, and the location of the healthcare institute. In addition to these limitations, the attitudes of policymakers impact the use of TR services [13,16]. [14].…”
Section: Discussionmentioning
confidence: 99%